Shear wave velocity changes induced by earthquakes and rainfall at the Rotokawa and Ngatamariki geothermal fields, Taupō Volcanic Zone, New Zealand. Issue 1 (4th December 2019) - Civilini, F; Savage, M K; Townend, J
SUMMARY: Fluid injection for geothermal production has the potential to produce subsidence and microseismicity that can incur heavy financial cost or hazard. Due to this, novel ways to monitor subsurface deformation to supplement existing methods are highly sought after. We use seismic ambient noise to obtain time-dependent measurements of shear velocity within the geothermal reservoirs of Rotokawa and Ngatamariki, two producing geothermal fields in the Taupō Volcanic Zone located in the central North Island of New Zealand and operated by Mercury Energy. We investigate the relationship between shear wave velocity changes and geothermal injection by selecting time periods at the fields when injection and production volumes were significantly altered: 2009–2010 at Rotokawa, when geothermal injection was quadrupled due to the start-up of a new power station, and 2012–2013 at Ngatamariki, the beginning of geothermal injection for electricity production at that field. Shear wave velocity changes are computed from the ambient noise cross-correlation coda using the Moving Window Cross-Spectral (MWCS) technique, with a reference stack encompassing all data prior to the change in injection rate and moving stacks of 10–50 d. Gradual positive and negative shear velocity changes with a periodicity of approximately 12 months were observed at both sites, with maximum amplitude of 0.06 ± 0.04 and –0.08 ± 0.03 per cent at Rotokawa and 0.07 ± 0.03 and –0.06 ± 0.02 per cent at Ngatamariki. We hypothesize that these changes are due to seasonal rainfall, as seismic velocities computed by ambient noise are sensitive to the filling and emptying of near-surface pore space. In addition to these gradual responses, we found several sharp negative changes in velocity that reach minimum values over a few days and then gradually equilibrate to prior values over a few weeks. The amplitude of these responses is between –0.03 and –0.07 per cent and coincides with regional and local earthquakes. We hypothesize that these responses are primarily produced by the creation of new fractures, the same mechanism that produces gradual groundwater level decreases at regional distances from earthquake epicentres. We analyse a periodic signal within the time-delay measurements and determine that it is at least in part caused by the MWCS window size smoothing the cross-coherence of the ambient seismic signal. We do not observe shear wave velocity changes coinciding with geothermal injection, which may suggest that the signal has lower amplitude compared to the seasonal and seismic responses. We use bandstop filters and polynomial curve fitting to remove the contribution of the seasonal signal, but see no evidence of a shear wave velocity response due to geothermal fluid injection.